RAQAMLI TA’LIM MUHITIDA AXBOROT TEXNOLOGIYALARIDAN FOYDALANGAN HOLDA TA’LIM SIFATINI OSHIRISH - Baltabaev, J. (SCIENCE and SOCIETY, 2025)
This article analyzed the possibilities and methods of using the electronic learning environment and improving the quality of education with the help of information technologies. At the same time, information was provided about the role of these technologies in education, their advantages, and future directions of development.